Tibial bone stress injuries, pubertal stage, bone properties and muscle strength in young competitive female gymnasts - Two years follow-up - Steinberg, N.; Elbaz, L.; Eliakim, A.; Nemet, D.; Dar, G. (Physical Therapy in Sport, 2026)
Objectives To examine the prevalence of young gymnasts with tibial bone-stress-injuries (BSIs) and its association with anthropometrics, pubertal-stage, bone properties, and muscle strength during two years.